Dendrochronological dating of kauri timbers from Browne's spar station (1832–1836), Mahurangi, Auckland, New Zealand. (June 2016) - Boswijk, Gretel; Brassey, Robert; Bader, Hans-Dieter; Adamson, Janice; Jones, Martin J.
Abstract: In New Zealand, timbers and other wooden objects have been found preserved in waterlogged prehistoric and historic-era archaeological sites, but dendrochronological analysis of such material is rare. In 2010 an archaeological investigation was carried out at the site of Browne's spar station, Mahurangi, Auckland (CE 1832–1836), documented as the earliest European settlement in the Auckland region. The station supplied spars to the British Admiralty and sawn timber to the Australian colonies. Timber features, made of kauri ( Agathis australis ), were present on the foreshore and included relics from a possible sawpit structure and a catwalk made from offcuts. Tree-ring samples were obtained from these to determine if they were associated with the spar station or from a later phase of activity. A four-timber tree-ring chronology was calendar dated to CE 1756–1831 and felling dates were obtained from three timbers. These indicated that: (a) the possible sawpit structure was built from trees felled between May and October 1832; (b) two offcuts used in the catwalk were from trees felled in late 1832 or early 1833; and (c) the catwalk was built in or after 1833. The tree-ring dates provide independent evidence that the timbers were contemporaneous with, and complement documentary information related to, the spar station. Analysis of wood samples also provides some insight into human behaviour regarding tree selection and the use of waste material. The spar station material is only the second waterlogged assemblage of kauri timbers to be analysed using dendrochronology in New Zealand and the first to be recovered from an inter-tidal context. The results demonstrate the potential for tree-ring analysis of waterlogged wood to provide accurate and precise dates for archaeological sites in New Zealand. Highlights: Relic timbers at an 1830s spar station were dendro dated to CE 1756–1832. Independent evidence that wooden features are associated with the spar station Provides insight into human behaviour regarding wood selection and use First wooden assemblage from an inter-tidal context to be tree ring dated in NZ